Manajemen Layanan Lembaga Pelatihan dan Pelayanan Bimbingan dan Penyuluhan Islam FDIK UIN Antasari Banjarmasin - Ilham Ilham; Ermalianti Ermalianti; Samsul Rani; Muhammad Rif'at (UIN Antasari Banjarmasin, 2022)
LP2BPI is one of unit in the faculty of Da’wah and Communication at UIN Antasari Banjramasin, which was managed by students and lecturer as it is stated in the Decree of Dean on personnel management. It is interesting to better understand the services management of this training, counseling service, and islamic guidance unit. The research method used is descriptive qualitative by employing field study. The object of the research is the management of the LP2BPI at FDIK. Service management of the training, counseling service, and islamic guidance unit (LP2BPI) Faculty of Da'wah and Communication Sciences UIN at Antasari Banjarmasin is on the basis of four management functions, starting from planning, organizing, implementing and supervising. The management worked well due to good communication between the leaders and all members of the unit.